Analisis Efektivitas Dan Efisiensi Penggunaan Aplikasi E-Faktur Dalam Prosedur Pembuatan Faktur Pajak Dan Pelaporan SPT Masa PPN Pada PT. XYZ - Suci, Hastidar Puspa Lenia; Samanto, Hadi; Rukmini (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to analyze the effectiveness and efficiency of the e-Faktur application in tax invoice issuance and VAT periodic return reporting at PT. XYZ. A qualitative descriptive approach was employed using interviews, observations, and document analysis. Effectiveness was measured through three indicators—accuracy of use, usefulness, and goal attainment—while efficiency was assessed through seven indicators including time, labor, and cost savings, accuracy, data security, reduced storage needs, and reporting convenience. The findings show that the effectiveness of e-Faktur reached 66.7%, categorized as moderately effective, where accuracy and usefulness were achieved but goal attainment was not optimal due to unstable internet connectivity. Meanwhile, efficiency reached 85.7%, categorized as efficient, with major advantages in saving time, cost, and storage space, although reporting convenience was still hindered by technical issues. These results highlight that e-Faktur contributes more significantly to efficiency than effectiveness, while also underlining the need for infrastructure improvements to optimize its benefits.